Train the Trainer: Hematopoietic Stem Cell Control of Trained Immunity - De Zuani, Marco; Frič, Jan (Frontiers in Immunology, 2022)
Recent evidence shows that innate immune cells, in addition to B and T cells, can retain immunological memory of their encounters and afford long-term resistance against infections in a process known as ‘trained immunity’. However, the duration of the unspecific protection observed in vivo is poorly compatible with the average lifespan of innate immune cells, suggesting the involvement of long-lived cells. Accordingly, recent studies demonstrate that hematopoietic stem and progenitor cells (HSPCs) lay at the foundation of trained immunity, retaining immunological memory of infections and giving rise to a “trained” myeloid progeny for a long time. In this review, we discuss the research demonstrating the involvement of HSPCs in the onset of long-lasting trained immunity. We highlight the roles of specific cytokines and Toll-like receptor ligands in influencing HSPC memory phenotypes and the molecular mechanisms underlying trained immunity HSPCs. Finally, we discuss the potential benefits and drawbacks of the long-lasting trained immune responses, and describe the challenges that the field is facing.